(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2020)
The aim of this paper is to analyze if the accounting system of Bosnia and Herzegovina (hereinafter B&H) budget is adequate and if it enables the measurement of public administration performance, as well as to give recommendations for future improvements. To achieve this, a survey was conducted among public employees working in the fields of finance, accounting and auditing at all levels of B&H government as well as among experts from the accounting and auditing field in B&H. The analysis of survey results revealed shortcomings in the accounting system in B&H budget evident in its inability to measure and report on the efficiency, effectiveness and economy of public spending, which reduces transparency and opens up an opportunity for misuse of public resources. According to the studies conducted thus far in this field, one of the most efficient ways to overcome this is to introduce specific cost and management accounting instruments into the accounting system of the budget, which would enable adequate measuring and reporting on the performance of public administration, thereby enhancing the transparency of public finances and accountability of public employees.